PLANT COMMUNITIES OF ALBANIA - A PRELIMINARY OVERVIEW - DRING, J.; HODA, P.; MERSINLLARI, M.; MULLAJ, A.; PIGNATTI, S.; RODWELL, J, (Annali di Botanica, 2002)
The phytosociological analysis of Albania was initiated by F. Markgraf in the 30ies, but still remains incomplete. This is a preliminary list of the plant communities resulting from the literature and from field research carried out during the last years and may represent a first contribution for further research. Many communities are described only by dominant species, other are quoted as nomina nuda. Some further syntaxa. probably present in the study area, are added.